On Symmetry in Physical Phenomena, Symmetry of an Electric Field and of a Magnetic Field - Pierre Curie; Andrzej Ziółkowski (przekład i komentarz) (Studia Historiae Scientiarum)
In this work, the classical concept of symmetry limited to geometric objects (figures and solids), which originated from ancient Greece, has been extended to allow for symmetry studies in other types of objects.